Influence of water temperature on feed intake, appetite control, and energy allocation in Atlantic salmon (Salmo salar) post-smolt - Lai, F.; Budaev, S.; Hundven, I. K.; Balseiro, P.; Handeland, S. O.; Rønnestad, I. (Frontiers in Physiology, 2025)
For ectothermal animals, such as the teleost Atlantic salmon (Salmo salar), temperature is a key environmental factor that influences metabolism, energy allocation and growth. However, the complex interactions among feed intake, appetite-regulating signalling pathways, gastrointestinal transit rates, and energy partitioning toward metabolism and growth across varying water temperatures remain poorly understood. In this study, feed intake, feed efficiency, somatic indices and growth were examined in Atlantic salmon post-smolts (ca. 200 g) acclimated to either 8°C, 12°C or 15°C for 8 weeks. Following the trial, a 24-h postprandial assessment was conducted to evaluate gastrointestinal (GI) transit, plasma metabolite dynamics and responses of appetite regulatory mechanisms. Feed intake (FI) and feeding rate (FIR) increased with temperature. A bell-shaped growth response was observed, with condition factor (K), specific growth rate (SGR), and relative growth rate (RGR) peaking at 12°C. Post prandial analysis revealed greater gastrointestinal content and faster GI-tract transit and feed processing rates at the highest temperatures. Notably, the most rapid and pronounced gallbladder refilling response was observed at 15°C. Elevated temperatures also enhanced postprandial metabolic responses of glucose, lactate, cholesterol, and triglycerides following digestion and processing of the ingested meal. Plasma ghrelin (Ghrl) levels decreased significantly at elevated temperature. Temperature negatively affected the ghrl1 expression in the stomach, and the expression dynamics of the orexigenic neuropeptide npya and anorexigenic pomca paralogues in the hypothalamus, which were lower at 15°C. Male maturing fish were observed with the increase of temperature, which associated with reduced feed intake and metabolic acclimations for reproductive development. These temperature-dependent physiological responses highlight the complex interplay between environmental factors and physiological acclimations in Atlantic salmon. A comprehensive understanding of these mechanisms is essential for optimizing growth performance and adaptive capacity in changing thermal environments.